2020
DOI: 10.1002/ped4.12213
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of infantile malignant solid tumors in beijing, China: A multicenter 10‐year retrospective study

Abstract: Importance Cancer is the main cause of death by disease in children. Children experience the highest incidence of cancer in the first year of life. However, there is no comprehensive registration system for children with tumors in China. Objective To summarize the diagnosis and treatment of infant cancer and analyze the status of standardized diagnosis and management among several treatment centers in Beijing, China, thereby providing evidence to guide further clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Cancer is the leading cause of death by disease in children. [13] For children with cancer, pain is a common and torturous symptom. [14] Although there are few accurate data reports on the current status of pain in children, studies have shown that almost all children with cancer experience pain.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the leading cause of death by disease in children. [13] For children with cancer, pain is a common and torturous symptom. [14] Although there are few accurate data reports on the current status of pain in children, studies have shown that almost all children with cancer experience pain.…”
Section: Discussionmentioning
confidence: 99%
“…1, we retrospectively analyzed the history data of 371 patients with retinoblastoma who were admitted to our hospital during 1st January 2007 and 31th December 2020 by searching our electronic medical record database using the key word "retinoblastoma". The inclusion criteria were as follows: (1) retinoblastoma diagnosed by computing tomography (CT) or magnetic resonance imaging (MRI); (2) aged between 3 and 13 years;…”
Section: Patientsmentioning
confidence: 99%
“…Retinoblastoma is one of the most common infantile malignant solid tumors, with a uniform incidence rate across population at 1 in 15,000-20,000 live births corresponding to about 9,000 new cases every year [1]. Although chemotherapy and radiation treatment aim to spare the eye, in some cases, enucleation (ie, removal of the entire eyeball) is considered the main treatment for end-stage ocular diseases [2]. An enucleation is performed as an outpatient procedure under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is the second leading cause of death among children aged 5 to 14 years after accidents, and more than one third of children diagnosed with tumors are before the age of five ( 1 ). In 2020, a retrospective survey of 938 children in Beijing over the past decade found that the three most common types of infant malignant solid tumors were retinoblastoma (39%), neuroblastoma (28.4%) and hepatoblastoma (14.2%) ( 2 ). Neuroblastoma is one of peripheral neuroblastic tumors (pNT).…”
Section: Introductionmentioning
confidence: 99%